A decade of temporal trends in overweight/obesity in youth with type 1 diabetes after the Diabetes Control and Complications Trial. Issue 4 (12th July 2014) - Baskaran, Charumathi; Volkening, Lisa K; Diaz, Monica; Laffel, Lori M
<x xml:space="preserve">Abstract</x> Background Youth with type 1 diabetes (T1D) are at risk for weight gain due to the epidemic of childhood overweight/obesity and common use of intensive insulin therapy; the latter resulted in weight gain in the Diabetes Control and Complications Trial. Objective To assess overweight/obesity prevalence and intensive insulin therapy use in youth with T1D over a decade and identify factors associated with weight status and glycemic control. Methods We obtained cross‐sectional data from four unique cohorts (1999, 2002, 2006, and 2009). Youth (N = 507, 49% male) were 8–16 yr old with T1D duration ≥6 months, A1c 6.0–12.0% (42–108 mmol/mol), and daily insulin dose ≥0.5 U/kg. Results Across cohorts, age, body mass index (BMI) percentile, and A1c ranged from 12.0 ± 2.2 to 12.8 ± 2.3 yr, 70 ± 22 to 72 ± 21, and 8.3 ± 1.0 (67 ± 11) to 8.5 ± 1.1% (69 ± 12 mmol/mol), respectively. Intensive insulin therapy use increased from 52 to 97% (p < 0.001) between 1999 and 2009. However, prevalence of overweight/obesity remained similar, 27% (1999), 36% (2002), 33% (2006), and 31% (2009) (p = 0.54), as did z‐BMI. In multivariate analysis, higher A1c was related to higher insulin dose (p < 0.01), less frequent blood glucose monitoring (p < 0.001), and non‐white race (p < 0.001); A1c was not related to z‐BMI, intensive insulin therapy, or cohort. z‐BMI was related to insulin dose (p < 0.005) but not intensive insulin therapy or cohort. Conclusions Despite near‐universal implementation of intensive insulin therapy, overweight/obesity prevalence in youth with T1D remained stable over a decade, similar to the general pediatric population. However, A1c remained suboptimal, underscoring the need to optimize T1D treatment to reduce future complication risk.